2016
DOI: 10.1128/aem.01751-16
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Culturability of Epiphytic Bacteria and Frequency of Biosurfactant Producers on Leaves

Abstract: To better characterize the bacterial community members capable of biosurfactant production on leaves, we distinguished culturable biosurfactant-producing bacteria from nonproducers and used community sequencing to compare the composition of these distinct cultured populations with that from DNA directly recovered from leaves. Communities on spinach, romaine, and head lettuce leaves were compared with communities from adjacent samples of soil and irrigation source water. Soil communities were poorly described b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 54 publications
4
23
0
Order By: Relevance
“…Notably, Xanthomonas represented 10%-40% of the whole bacterial communities of fruits, leaves and flowers, while, similarly to other studies, was not found in a significant abundance in the rhizosphere (Ottesen et al 2013). Xanthomonas was also found as a dominant member in the microbiome of field grown Romain lettuce phyllosphere (Rastogi et al 2012;Burch et al 2016). In particular, one large scale microbiome study with samples collected from 88 different lettuce growing areas has identified Xanthomonas to be present in about a third of all samples, where it comprises, on average, 4% of the lettuce microbiome (Rastogi et al 2012).…”
Section: Xanthomonas In the Plant Microbiomesupporting
confidence: 81%
“…Notably, Xanthomonas represented 10%-40% of the whole bacterial communities of fruits, leaves and flowers, while, similarly to other studies, was not found in a significant abundance in the rhizosphere (Ottesen et al 2013). Xanthomonas was also found as a dominant member in the microbiome of field grown Romain lettuce phyllosphere (Rastogi et al 2012;Burch et al 2016). In particular, one large scale microbiome study with samples collected from 88 different lettuce growing areas has identified Xanthomonas to be present in about a third of all samples, where it comprises, on average, 4% of the lettuce microbiome (Rastogi et al 2012).…”
Section: Xanthomonas In the Plant Microbiomesupporting
confidence: 81%
“…4). Many members of this genus have been found to possess gliding motility (12,57,58), while flagellar motility in members of the family Flavobacteriaceae is almost unheard of (59), and recent isolates of the order Flavobacteriales from leaf surfaces have also been reported as biosurfactant producers (53). While the role of chemotaxis was not measured directly, it is possible that chemotactic organisms are enriched at the rim of the ceramic plate, where the substrate concentration is highest thanks to the low cell density.…”
Section: Discussionmentioning
confidence: 99%
“…The plant phyllosphere harbors diverse microbial communities and bacteria constitute the dominant population (Kembel et al, 2014). The mechanisms by which bacteria colonize and survive on leaf surfaces remain largely unknown (Burch et al, 2016). Healthy epidermal plant cells constantly leak organic and inorganic molecules, such as amino acids, sugars, and various salts to their surfaces; this may facilitate the colonization of microflora by interacting with the plant phyllosphere (Knief et al, 2012;Burch et al, 2016).…”
mentioning
confidence: 99%